KONSEP I‘JAZ AL-QUR’AN MENURUT PEMIKIRAN MU‘TAZILAH - Ilham Abiyusuf; Fadhli Maulana Ihsan; Pakhrurrozi; Fauzan Azima Syafiuddin (Makkah: Journal Of Islamic Studies, 2025)
: This article discusses the theory of i‘jāz al-Qur’an (the inimitability of the Qur’an) and the critiques offered by Muslim scholars toward various interpretations of it. The Qur’an, as the eternal miracle of the Prophet Muhammad (peace be upon him), possesses an unmatched uniqueness in terms of language, structure, and meaning. Throughout Islamic intellectual history, scholars have provided diverse explanations regarding the essence of this miraculous nature. Some emphasized the rhetorical beauty and linguistic structure of the Qur’an, while others focused on its profound meanings and universal truths. This study also examines criticisms of specific theories such as al-sarfah, proposed by certain Mu‘tazilite scholars, which are considered to diminish the true miraculous quality of the Qur’an. Using a qualitative, library-based analytical approach, this article concludes that the inimitability of the Qur’an lies in the perfect harmony of its eloquence, depth of meaning, and timeless truth.